Rural dynamics and development - Narayana Reddy, G. (Allahabad, India : Chugh Publications, 1986)
Articles with reference to India.
Spine title: Rural dynamics & development.
Includes bibliographies.
Keywords: Rural development -- India; India -- Rural conditions